(untitled) (Research, Society and Development, 2020)
The aim of the study was to count lactic bacteria in strawberry-flavored fermented milk beverages, in portions of 90 grams, marketed in supermarkets in Vitória da Conquista – Bahia, Brazil. Four units of samples were collected from each of the four marks chosen, arbitrarily, in 2 lots, with a total of 32 samples. The methodology adopted was that described by the American Public Health Association (APHA), which involves the following steps: serial dilution of the sample, plating of dilutions by pour plate technique with growth medium overlayer, incubation and plate counting of colonies. Of the samples evaluated, only the sample A1 fit the standard of Normative Nº 46 of October 23, 2007, with viable population bacteria of 106 CFU/g. It is believed that this result may be due to high storage temperatures in addition to the inclusion of fruit pulps that can also influence the reduction of the number of lactic bacteria, an evidenced fact in yogurts. It is up to the establishments and the Municipal Sanitary Surveillance to carry out the inspection so that such products have their functional properties ensured.